OWE-29 Can digital skeletal muscle index predict palliative chemotherapy uptake before patients undergo endoscopic pancreatic biopsy?. (June 2019) - Jalal, M; Campbell, JA; Wadsley, J; Hopper, AD
Abstract : Introduction: An endoscopic ultrasound guided biopsy (EUS-B) is required prior to treatment with palliative chemotherapy for patients with suspected pancreatic ductal adenocarcinoma (PDAC). Given the urgency of treatment, EUS-B is often done prior to oncological assessment after which a significant proportion of patients do not take up chemotherapy. Low skeletal muscle index (SMI), termed sarcopenia, is common in PDAC and has been associated with poor outcomes. We aimed to assess if novel digital software can calculate SMI using a computerised tomography (CT) image to predict palliative chemotherapy uptake in patients with suspected PDAC, and streamline EUS-B. Methods: Patients who underwent an EUS-B showing PDAC between Jan 2016 and Dec 2017 with a CT scan performed within a month prior to biopsy were included in the study. SMI was calculated by a single slice CT image taken at the level of the third lumbar vertebra. Software was used to identify skeletal muscle (sliceOmatic, Tomovision). Sarcopenia was defined as SMI<41(female) and <53 cm 2 /m 2 (male). Body mass index (BMI), performance status, demographic data were also compared between patients that went on to receive chemotherapy and those who did not. Results: EUS-B confirmed PDAC in 85 eligible patients during the study (median age 70;41–84 years). A total of 61/85(71%) of patients received at least one dose of chemotherapy. Sarcopenia was present in 57/85 (57.6%). Despite a raised BMI of >25 in 41/85 (48.1%) of the patients, sarcopenia was present in 25 (61.0%) of them. Patients who did not take up chemotherapy had a lower SMI (40.5 vs 45.2 cm 2 /m 2, p =0.04) and a poorer mean performance status (1.25 vs 0.7: t-test p =0.002). There was no difference in BMI (26.8 vs 24.6 p=0.10) in patients that did and did not take up chemotherapy. No patients with a performance status of 3 (n=3) or age >80 (n=5) proceeded to chemotherapy. In those having chemotherapy, survival was higher in non-sarcopenic patients compared to sarcopenic patients (11.8 vs 7.7 months, p =0.04). Survival was similar in sarcopenic patients having chemotherapy and non-sarcopenic patients who did not have chemotherapy (7.7 vs 7.4 months p =0.5). Patients with performance status ≥2 and sarcopenia were much less likely to receive chemotherapy compared to those with performance status 0–1 without sarcopenia (83.9% vs 37.5%, p = 0.02). Conclusion: Patients with PDAC and a performance status of ≥2 and low SMI were significant less likely to take up chemotherapy and had poorer survival. SMI measurement could act as part of a decision tool to assess suitability of patients to triage patients for rapid EUS-B, or clinical assessment prior to considering chemotherapy.